Bureaucratic Governance For Developing Administration İn Madrasah Aliyah Ma’arif: (Study in 2017-2021) - Abdul Hadi; V. Rudy Handoko; Rachmawati Novaria (Asian Journal of Management, Entrepreneurship and Social Science, 2024)
This research aims to explore bureaucratic governance in the development of educational administration at Madrasah Ma'arif Ambulu, a religious educational institution belonging to LP Ma'arif NU. In the context of globalization, religious education faces competitive challenges, especially in terms of bureaucratic governance which is considered less professional. The research uses a descriptive qualitative approach, with data collection through interviews, observation and documentation. Data analysis includes stages of condensation, collection, display, and conclusion of findings. Research findings produce a bureaucratic governance model consisting of three main elements: governance rules, authority, and work distribution. Regulatory governance involves internal and external assessment processes. Authority governance consists of custom authority which integrates rational legal and transformative charisma authority models. Work distribution governance includes quality assurance of madrasa leaders, resource support, staff supervision, internal-external analysis, and preserving work values while meeting modernization needs. All staff are distributed according to their commitment and competence in the areas of quality achievement, administration and religion. This model aims to increase the effectiveness of educational administration at Madrasah Ma'arif Ambulu and contribute to the context of the development of religious education more broadly.